An Expressive Dilemma Generation Model for Players and Artificial Agents - Harmon, Sarah (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2016)
Dilemma scenarios and knowledge of social values support engaging and believable narrative gameplay. Previous work in dilemma generation has explored scenarios involving utility payoffs between two to three people. However, these models primarily require character relationships as preconditions, and do not extend to more complex choices that relate only to causes and values. This paper builds upon past work to create an expressive model of dilemma categorization for player and non-player characters.